Holocene palaeoceanographic evolution of the Iskenderun bay, South-Eastern Turkey, as a response to river mouth diversions and human impact - SPEZZAFERRI, S.; BASSO, D.; KORAL, H. (Mediterranean Marine Science, 2000)
A quantitative study of benthic foraminifera, sediment texture and composition from two cores was performed to unravel the environmental evolution of the Iskenderun Bay (eastern Turkey) in the Holocene. Core 29 (NE Iskenderun Bay) consists of clay and silt from the top of the core down to 35 cm with dominant bioclasts (coral Cladocora caespitosa) from 35 cm down to the bottom of the core. Core 92, located near an ancient Ceyhan River mouth (Yumurtalik), consists of sandy and silty sediment passing to homogeneous clay and silt at about 48 cm from the top. Several grab samples show very coarse biogenic detritus covered by a centimetric veneer of sandy silt and clay. Radiocarbon dating of corals, molluscs and algae from core 29 and five selected grab samples, the sediment and foraminiferal study indicate that at least three pulses of muddy sedimentation occurred in the bay. (1) An older pulse (about 3700 yrs BP) related to the large-scale forest clearing (Beysheir Occupation Phase). (2) Another pulse coincides with a major delta progradation of the Ceyhan River at about 2140 years BP. (3) A younger pulse follows the diversion of the Ceyhan River mouth toward Yumurtalik, from the Middle Age to 1935. Species interpreted as tolerant of low salinity indicate that the influence of the Ceyhan was minor when the river drained directly into the Mediterranean Sea (approximately 2000 years BP) and progressively increased when the river diverted towards Yumurtalik.